Modelling eruptive source parameters in distributed volcanic fields - Gallant, Elisabeth; Cole, Lawrence; Connor, Chales; Donovan, Amy; Molisee, Danielle; Morin, Julie; Walshe, Rory; Wetmore, Paul (Volcanica, 2021)
Vent opening hazard models are routinely used as inputs for assessing distal volcanic hazards (lava flows, tephra fallout) in distributed volcanic fields. These vent opening hazard models have traditionally relied on the location of mapped vents; seldom have they taken into account how vents are linked in space and time. We show that inputs needed to appropriately model distal hazards are fundamentally different than thoses required to model near-vent hazards (ground deformation). We provide a computational model to obtain more appropriate eruptive source parameters (ESPs) for distal volcanic hazard sources and show the utility of our code through three examples. The code’s strength is that it links events based on the spatio-temporal relationships of vents through heirarchical clustering. The development of the code and its strenghts and weaknesses are discussed. This work challenges previous ideas about ESPs and we hope this work leads to further improvement in hazard assessment methods.